2014
DOI: 10.1007/s12031-014-0246-2
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoid 2-Arachidonylglycerol Protects Primary Cultured Neurons Against LPS-Induced Impairments in Rat Caudate Nucleus

Abstract: Inflammation plays a pivotal role in the pathogenesis of many diseases in the central nervous system. Caudate nucleus (CN), the largest nucleus in the brain, is also implicated in many neurological disorders. 2-Arachidonoylglycerol (2-AG), the most abundant endogenous cannabinoid and the true natural ligand for CB1 receptors, has been shown to exhibit neuroprotective effects through its anti-inflammatory action from proinflammatory stimuli in hippocampus. However, it is still not clear whether 2-AG is also abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 38 publications
5
19
0
Order By: Relevance
“…URB602 suppresses excessive COX-2 expression in response to Hcy in the cultured CN neurons through the CB1 receptor, not the CB2 receptor URB602, a selective inhibitor of MAGL activity, is known to elevate the levels of endogenous 2-AG and enhance 2-AG-mediated signaling in neurons, without affecting the level of arachidonoyl ethanolamide (anandamide, AEA), another endocannabinoid ligand [37]. As a key player in inflammation, COX-2 is markedly elevated by a variety of stimulation of inflammation [12,25,41]. Hcy serves as an inducer of proinflammatory response to induce neural injury.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…URB602 suppresses excessive COX-2 expression in response to Hcy in the cultured CN neurons through the CB1 receptor, not the CB2 receptor URB602, a selective inhibitor of MAGL activity, is known to elevate the levels of endogenous 2-AG and enhance 2-AG-mediated signaling in neurons, without affecting the level of arachidonoyl ethanolamide (anandamide, AEA), another endocannabinoid ligand [37]. As a key player in inflammation, COX-2 is markedly elevated by a variety of stimulation of inflammation [12,25,41]. Hcy serves as an inducer of proinflammatory response to induce neural injury.…”
Section: Resultsmentioning
confidence: 99%
“…URB602 inhibits the phosphorylation of NF-κB and degradation of IκB-α in response to Hcy in the primary CN neurons via the CB1 receptor A preceding study showed that the NF-κB signaling pathway was involved in the lipopolysaccharide (LPS)-induced or Hcy-induced neuroinflammation in the hippocampus and CN [14,25,40,41]. To determine whether this signaling pathway is involved in the URB602 suppression of COX-2 induced by Hcy in the CN neurons, we detected the phosphorylation level of NF-κB in the CN neurons.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations